2020
DOI: 10.3390/children7120308
|View full text |Cite
|
Sign up to set email alerts
|

Does Sex Dimorphism Exist in Dysfunctional Movement Patterns during the Sensitive Period of Adolescence?

Abstract: This study aimed to investigate sex difference in the functional movement in the adolescent period. Seven hundred and thirty adolescents (365 boys) aged 16–17 years participated in the study. The participants performed standardized Functional Movement Screen™ (FMSTM) protocol and a t-test was used to examine sex differences in the total functional movement screen score, while the chi-square test was used to determine sex differences in the proportion of dysfunctional movement and movement asymmetries within th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 30 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…FMS™ Functional Movement Screen™ 3 in the UK [4,50,51], 2 in Croatia [56,57] and a single study each from India [44], Iran [40] and Moldova [54]. Fourteen of the study designs were cross-sectional [4,40,44,[46][47][48][49][51][52][53][54][55][56][57], and a single study each was a cluster randomised controlled trial [45], randomised controlled trial [43], quasi-experimental [41], matched pairs experiment [50], and a single-arm trial [42]. The sample sizes ranged from 20 [42] to > 1000 [44].…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…FMS™ Functional Movement Screen™ 3 in the UK [4,50,51], 2 in Croatia [56,57] and a single study each from India [44], Iran [40] and Moldova [54]. Fourteen of the study designs were cross-sectional [4,40,44,[46][47][48][49][51][52][53][54][55][56][57], and a single study each was a cluster randomised controlled trial [45], randomised controlled trial [43], quasi-experimental [41], matched pairs experiment [50], and a single-arm trial [42]. The sample sizes ranged from 20 [42] to > 1000 [44].…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…All studies had minimal missing data, and all used the FMS™ assessment tool [2,3], which is reported to be both valid and reliable in the assessment of functional movement among the included samples. The majority of studies (89%; 17/19 studies) examined potential correlates [4,40,41,[43][44][45][46][47][48][49][51][52][53][54][55][56][57] in a valid and reliable manner.…”
Section: Overview Of Studies' Risk Of Biasmentioning
confidence: 99%
“…Of the available studies, some include both boys and girls [32,40,41,44 Of the studies that included both boys and girls, some studies have not reported sex differences in the FMS [57,77,78,82]. Other studies have reported no significant differences in the FMS scores between boys and girls [36,38,41,44,48,49,58,62,63,76,81,83,86,87,[89][90][91]93,99,103,110]. Fewer studies have reported that girls perform better than boys [32,40,45,54,55,59,88,108] and even fewer studies report that boys perform better than girls [107,111].…”
Section: Sex and Age Differences In The Performance On The Fmsmentioning
confidence: 99%
“…Functional Movement. A functional movement implies an optimal range of motion (flexibility of the soft tissue and mobility of the joints), balance, and neuromotor postural control of the body regions involved in the specific movement [ 34 , 35 , 40 , 41 ].…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation